Correlation of Working Style to Stress, Coping Mechanism and Metabolic Syndrome Risk in Sedentary Workers - Atmaka, Dominikus Raditya; Arini, Shintia Yunita; Irwanto, Bian Shabri Putri; Agustin, Asri Meidyah; Nastiti, Aliffah Nurria; Prianto, Muh. Agus; Rahman, Andi Suci (Universitas Airlangga, 2025)
Introduction: Emotional eating, as a method of stress coping mechanism in workers, makes a person tend to consume more energy daily. Uncontrolled daily intake will lead to a high probability of a person developing metabolic syndrome in the future. The aim of this study is to analyze the relationship between working style to stress, coping mechanisms, and metabolic syndrome risk in sedentary workers. Method: This research is a cross-sectional study conducted at Kalla Group. Measurement of blood biochemistry (total cholesterol, blood glucose and uric acid) used FORA 6 Plus, blood pressure was measured using Omron digital sphygmomanometer 7130, waist circumference using Seca 201 measuring tape, and height using GEA microtoise. Measurements of body composition used Omron Karada Scan Hbf 375 Body Fat Composition Monitor Bioimpedance Analyzer. Stress was measured using Kessler Psychological Distress Scale K10 instrument. Coping mechanism was measured using Carver’s COPE Inventory. Result: Significant correlations were found for cholesterol levels (p = 0.044), waist circumference (p = 0.036), blood pressure (p = 0.042), and muscular percentage (p = 0.032). No significant correlations were found between working style for stress level (p = 0.683), coping mechanisms (p = 0.744), blood glucose (p = 0.128), uric acid (p = 0.380), visceral fat percentage (p = 0.128), and fat mass (p = 0.547). Conclusion: Significant correlations were found between working style for cholesterol levels, waist circumference, blood pressure, and muscular percentage, suggesting that different working styles may influence these health aspects.